Maḥāsin al-Syarī‘ah on The Implementation of Mahḍah Worship: Overview of Islamic Legal Philosophy - Primadhany, Erry Fitrya; Angelia, Novita Mayasari; Angraeni, Novita; Jarkani, Baihaki (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
For muslims, Islamic law, particularly in matters of worship, is not only a formality; rather, it is an obligatory for Muslims to fully aware of why they are prescribed to them; hence, it is vital to study its merits. This article focuses on the preeminence of Islamic law (maḥāsin al-syarī‘ah) and the preeminence of Islamic law in the implementation of mahḍah (obligatory) Worship from the Islamic legal philosophy standpoint. This article presents qualitative and conceptual normative law research. Our findings suggest that the primacy of Islamic law (maḥāsin al-syarī‘ah) examines the aim and nature of law so that it can be readily accepted and comprehended by humanity. Islamic law is a framework for managing human life, the essence of which is syarī‘ah, which seeks to preserve the good and prevent the harm. As a type of human subservience to Allah, Islamic law's application of worship possesses the virtue of servitude. In the context of worship, purification comes first, with the highest emphasis being that our state is pure and holy when doing worship. Second, the virtue of prayer as a reminder of God's blessings and as a sign of Muslims' sincerity toward the Creator. The third reason for fasting is to become more pious and grateful for Allah's blessings. The four qualities of tithing help a person develop a charitable character. And finally, the trip signifies a readiness to make sacrifices in the removal of property.